2020
DOI: 10.3390/molecules25215000
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Neurochemical Effects of Extra Virgin Olive Oil Total Phenolic Content and Sideritis Extract in Female Mice

Abstract: The aim of this study was to determine the cognitive and behavioral effects of extra virgin olive oil total phenolic content (TPC) and Sideritis (SID) extracts in female mice, and identify the associated neurochemical changes in the hippocampus and the prefrontal cortex. All animals received intraperitoneal low or high doses of TPC, SID or vehicle treatment for 7 days and were subjected to the Open Field (OF), Novel Object Recognition (NOR) and Tail Suspension Test (TST). The prefrontal cortex and hippocampus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…In the literature, there are different kinds of molecules with multifunctional properties that contain the N -benzyl-piperidine moiety associated with MAO and acetylcholinesterase inhibitor activity [ 55 ]. Furthermore, the antioxidant properties of phenolic compounds derived from olive oil have been widely demonstrated, which also have beneficial neurochemical effects [ 56 , 57 ]. Considering the similarity between the MAO metabolites and the polyphenolic compounds, it was reasonable that the presence of a phenolic portion could favor one enzyme and also have some effect on others.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are different kinds of molecules with multifunctional properties that contain the N -benzyl-piperidine moiety associated with MAO and acetylcholinesterase inhibitor activity [ 55 ]. Furthermore, the antioxidant properties of phenolic compounds derived from olive oil have been widely demonstrated, which also have beneficial neurochemical effects [ 56 , 57 ]. Considering the similarity between the MAO metabolites and the polyphenolic compounds, it was reasonable that the presence of a phenolic portion could favor one enzyme and also have some effect on others.…”
Section: Discussionmentioning
confidence: 99%
“…On this basis, the ratio between omega 3 and 6 in the triple omega microcapsules might contribute to the increase in the values of neurotransmitters. Kokras et al (2020) reported that olive oil has a promising effect against cognitive decline and mental disorder due to its content of biological active substances that increase neurotransmitters.…”
Section: Re Sults and Discussionmentioning
confidence: 99%
“…Treatment of aged, non-transgenic, and APP-transgenic mice with S. scardica extract (and S. euboea extract) enhanced cognition and reduced the amyloid plaque burden in transgenic mice [ 28 ]. Nevertheless, results were not equally promising when female mice were used while high doses induced a dose-dependent sedative effect [ 29 ]. More recently, S. scardica water extract was demonstrated to preserve memory in mice with scopolamine-induced dementia [ 30 ].…”
Section: Introductionmentioning
confidence: 99%